1990
DOI: 10.1002/jor.1100080511
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro mechanical and histological study of acute stretching on rabbit tibial nerve

Abstract: Peripheral nerves are often mechanically stretched in association with trauma to extremities, resulting in varying degrees of impairment of nerve function. However, little is known about the biomechanical properties of peripheral nerves and limits of stretching that the nerve may undergo before structural changes occur. Also, the injury pattern of nerves under stretching is poorly understood. In the present study, fresh rabbit tibial nerves (n = 18) were harvested. Nine nerves were stretched to failure in an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
4
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(122 citation statements)
references
References 22 publications
4
109
4
5
Order By: Relevance
“…It has been reported that the peripheral nerve's perineurium appears to tolerate distraction force mainly during nerve lengthening and that peripheral nerve viscoelasticity is maintained as long as the perineurium remains. 18,19 In our study, the length between the ring and the marking suture as well as the overlapping length of both nerve stumps was significantly increased in proportion to the distraction period. However, the lengthened amount was less than the distraction amount.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…It has been reported that the peripheral nerve's perineurium appears to tolerate distraction force mainly during nerve lengthening and that peripheral nerve viscoelasticity is maintained as long as the perineurium remains. 18,19 In our study, the length between the ring and the marking suture as well as the overlapping length of both nerve stumps was significantly increased in proportion to the distraction period. However, the lengthened amount was less than the distraction amount.…”
Section: Discussionsupporting
confidence: 47%
“…In physiological conditions, the peripheral nerve trunk usually becomes slightly slack. 18 Thus, many of the distractions were required to overcome such slack in the nerve trunk. After completion of the 20-day distraction, the distance between the ring and the marking suture significantly increased to 12.1 AE 0.8 mm from the initial 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Under similar experimental conditions, it was found that fresh rabbit tibial nerve had an ultimate stress of 11700 Ϯ 700 kPa and an ultimate strain of 0.385 Ϯ 0.020 [17]. Another experiment documented an ultimate strain of 0.557 [18].…”
Section: Figmentioning
confidence: 99%
“…12,18 Peripheral nerve mechanical failure occurs at 27% increase in length. 24 Decrease in blood flow causing patching ischemia and/or tear of the intraneural connecting tissue causing hemorrhage and/or necrosis are considered the pathophysiology behind the symptoms. Continuous high levels of compression or elongation could lead to an increase of the intraneural venous pressure, which produces endoneural edema.…”
Section: Discussionmentioning
confidence: 99%